Electronic Properties and Dissociative Photoionization of Thiocyanates, Part III. The Effect of the Group’s Electronegativity in the Valence and Shallow-Core (Sulfur and Chlorine 2p) Regions of CCl3SCN and CCl2FSCN - Rodríguez Pirani, Lucas (2017)
Both photoelectron spectroscopy (PES) data and PhotoElectron-PhotoIon-Coincidence (PEPICO) spectra obtained from a synchrotron facility have been used to examine the electronic structure and the dissociative ionization of halomethyl thiocyantes in the valence and shallow-core S 2p and Cl 2pregions. Two simple and closely related molecules, namely, CCl3SCN and CCl2FSCN, have been analyzed to assess the role of halogen substitution in the electronic properties of thiocyanates. The assignment of the He(I) photoelectron spectra has been achieved with the help of quantum chemical calculations at the outer-valence Green’s function (OVGF) level of approximation. The first ionization energies observed at 10.55 and 10.78 eV for CCl3SCN and CCl2FSCN, respectively, are assigned to ionization processes from the sulfur lone pair orbital [n(S)]. When these molecules are compared with CX3SCN (X = H, Cl, F) species, a linear relationship between the vertical first ionization energy and electronegativity of CX3 group is observed. Irradiation of CCl3SCN and CCl2FSCN with photons in the valence energy regions leads to the formation of CCl2X⁺ and CClXSCN⁺ ions (X = Cl or F). Additionally, the achievement of the fragmentation patterns and the total ion yield spectra obtained from the PEPICO data in the S 2p and Cl 2p regions and several dissociation channels can be inferred for the core-excited species by using the triple coincidence PEPIPICO (PhotoElectron-PhotoIon-PhotoIon-Coincidence) spectra.